The Effect of Facilities Management and Work Discipline on Employee Performance: Study in one of Regional Companies in Medan City - Maya Maya; Etika Kristiani (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
The problem addressed in this research is the existence of employees who lack understanding of their duties, functions, and responsibilities, resulting in delayed completion of tasks. Furthermore, the level of employee discipline is low, as seen from the high rate of absenteeism. The employees' performance is also suboptimal, and the office lacks adequate facilities. This study aims to investigate the influence of facility management on employee performance, discipline on employee performance, and the combined effect of facility management and discipline on employee performance. The population of this research is employees of a regional company in Medan city, consisting of 50 respondents. The data collection technique used in this research is saturated sampling, and the data sources are primary and secondary data. Quantitative analysis and multiple linear regression analysis are employed in data analysis. The results of the multiple regression analysis show that facility management and discipline have a positive and significant effect on employee performance. The partial test results show that facility management has a positive and significant effect on employee performance, while the discipline variable also has a positive and significant effect on employee performance. The coefficient of determination is 0.525 or 52.5%. This indicates that 52.5% of the dependent variable, which is employee performance, can be explained by the facility management and discipline variables in the model, while the remaining 47.5% is influenced by other variables outside the model.